Interferon-γ/Interleukin-27 Axis Induces Programmed Death Ligand 1 Expression in Monocyte-Derived Dendritic Cells and Restores Immune Tolerance in Central Nervous System Autoimmunity - Casella, Giacomo; Rasouli, Javad; Thome, Rodolfo; Descamps, Hélène C.; Vattikonda, Asrita; Ishikawa, Larissa; Boehm, Alexandra; Hwang, Daniel; Zhang, Weifeng; Xiao, Dan; Park, Jeongho; Zhang, Guang-Xian; et al. (Frontiers in Immunology, 2020)
Tolerance induction by intravenous (i.v.) injection of autoantigens has been explored for therapy of autoimmune diseases, including multiple sclerosis. However, because of the complexity of the immune system none of our current therapies have proved to be fully effective. Here, we describe a pathway whereby i.v.-injected autoantigen into mice with experimental autoimmune encephalomyelitis (EAE) induces IFN-γ secretion by CD4+ T cells, triggering IL-27 production by conventional dendritic cells type 1 (cDC1). IL-27 induces PD-L1 expression, via STAT3 activation, in monocyte-derived DCs (moDCs) infiltrated into the CNS of mice with EAE. PD-L1 interaction with PD-1 on pathogenic CD4+ T cells then promotes their apoptosis/anergy, resulting in disease amelioration. Our findings identify a key role of the IFN-γ/IL-27/PD-L1 axis, involving T cells/cDC1/moDCs in the induction of i.v. tolerance, which defines a pathway whereby autoantigen-induced IFN-γ secretion restores immune tolerance in CNS autoimmunity.